KOTA-KOTA EKS KERESIDENAN KEDU (KAJIAN MORFOLOGI KOTA BERSEJARAH) - Dwi Pradnyawan (Berkala Arkeologi, 2019)
The cities of the former Kedu Residency are part of cities in Java that have experienced growth and change over time. Although not a big cities in its time, the cities of the former Kedu Residency show an important role in the interior of Central Java. Its distinctive history in the 19th and 20th centuries formed a city center with an interesting city structure to study. This study aims to study the urban centers of the former Kedu Residency, namely the City of Magelang, Purworejo, Temanggung, Wonosobo, and Kebumen through urban morphology approach by observing the forms (morpho) of the city, such as urban tissue or city shaped, road tissue, land arrangements and buildings. The morphology analysis of the city in the urban centers of the former Kedu Residency shows the interesting facts, namely the development of the city, specifically the city center, from time to time while maintaining the basic characteristics of the traditional city morphology.